Low‐dose whole‐lung irradiation in severe COVID‐19 pneumonia: a controlled clinical trial. Issue 4 (20th August 2021) - Mousavi Darzikolaee, Nima; Kolahdouzan, Kasra; Abtahi, Hamidreza; Kazemizadeh, Hossein; Salehi, Mohammadreza; Ghalehtaki, Reza; Bayani, Reyhaneh; Pestehei, Seyed Khalil; Ghazanfari, Tooba; Ebrahiminasab, Fatemeh; Salarvand, Samaneh; Haddad, Peiman; et al.
Abstract: Introduction: The COVID‐19 pandemic has caused significant morbidity and mortality thus far. Considering the historical uses of high‐voltage X‐ray beams for unresolvable pneumonia, we aimed to assess whether low‐dose whole‐lung irradiation (WLI) could provide any benefits for patients with refractory COVID‐19 pneumonia. Methods: Eleven patients with refractory COVID‐19 pneumonia were treated with WLI to a total dose of 1 Gy and compared to 11 patients in a matched control group from June to November 2020. The study's primary endpoint was improvement of chest X‐ray severity score (CXRS), followed by changes in mean oxygen (O2) saturation and 28‐day mortality as secondary endpoints. Results: The final CXRS was significantly lower in the WLI group (8.7 ± 2.5) compared to the control group (12.3 ± 3.3) (P: 0.016). Change of CXRS from the first to the last chest X‐ray was −2.2 ± 3.1 for the WLI group and 0.7 ± 3.9 for the control group, which showed a trend for lower CXRS in the WLI group (U = 30, p: 0.085). Mean O2 saturation showed insignificant improvement in the first 24 hours after radiotherapy (mean difference: 2.5 ± 4.1, Z=−1.6, P value: 0.11). Overall survival after 28 days was 32% in the WLI group and 11% in the control group ( P : 0.48). The reason for death in many patients was not merely respiratory failure, but also other adverse situations like pneumothorax, cardiogenic shock and pulmonary thromboembolism. Conclusions: Low‐dose WLI could improve the CXR severity score and O2 saturation in severely ill COVID‐19 patients, but larger studies are required to determine its impact on mortality. Abstract : Low dose whole lung irradiation could improve the chest X‐ray severity score and oxygen saturation in severely ill COVID‐19 patients, but larger studies are required to determine its impact on mortality.